2008
DOI: 10.1186/1475-2859-7-17
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Brugmansia candida Hyoscyamine 6beta-Hydroxylase gene in Saccharomyces cerevisiae and its potential use as biocatalyst

Abstract: Background: Tropane alkaloids, mainly hyoscyamine and scopolamine, are widely used in medicine due to their anticholinergic activity. Scopolamine has a higher demand being the more valuable alkaloid due to its fewer side effects and higher physiological activity. Anisodamine (6β-hydroxyhyoscyamine) is the intermediate in the conversion of hyoscyamine into scopolamine. Current studies report that this alkaloid is potentially applicable in medicine. The gene that codifies for Hyoscyamine 6-β hydroxylase, the enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
(28 reference statements)
2
14
0
1
Order By: Relevance
“…Consistent with our findings, a similar phenomenon was previously reported in H. niger (Hashimoto et al 1993). Recently, a H6H gene from Brugmansia candida was functionally expressed in yeast indicating a good potential for use as a biocatalyst (Cardillo et al 2008). Because the complex structures of alkaloids make chemical synthesis complicated and expensive, our genetically engineered bacterial strains which can express bioactive product provide an alternative promising bioreactor to produce scopolamine as a new biocatalyst.…”
Section: Bioconversion Of Hyoscyamine To Scopolamine In E Colisupporting
confidence: 90%
“…Consistent with our findings, a similar phenomenon was previously reported in H. niger (Hashimoto et al 1993). Recently, a H6H gene from Brugmansia candida was functionally expressed in yeast indicating a good potential for use as a biocatalyst (Cardillo et al 2008). Because the complex structures of alkaloids make chemical synthesis complicated and expensive, our genetically engineered bacterial strains which can express bioactive product provide an alternative promising bioreactor to produce scopolamine as a new biocatalyst.…”
Section: Bioconversion Of Hyoscyamine To Scopolamine In E Colisupporting
confidence: 90%
“…When the two varieties are compared, it can be seen that the H6H hydroxylase and epoxidase activities of the Argentinean clones are significantly higher than that of the Colombian clones (p = 0.0094 and 0.0265, respectively). Hyoscyamine (1) biotransformation processes carried out with a recombinant Saccharomyces cerevisiae strain carrying the h6h cDNA obtained from Argentinean B. candida plants showed similar results, probably related to the nature of the isolated gene [22,23]. Cardillo et al [23] reported that the recombinant en- zyme converted mainly hyoscyamine into anisodamine.…”
Section: Dwmentioning
confidence: 83%
“…Hyoscyamine (1) biotransformation processes carried out with a recombinant Saccharomyces cerevisiae strain carrying the h6h cDNA obtained from Argentinean B. candida plants showed similar results, probably related to the nature of the isolated gene [22,23]. Cardillo et al [23] reported that the recombinant en- zyme converted mainly hyoscyamine into anisodamine. The specific hydroxylase activity measured in yeast extracts was 10 times higher than the epoxidase activity.…”
Section: Dwmentioning
confidence: 83%
“…Acetyltropic acid (3-acetoxy-2-phenylpropanoic acid) is an important intermediate for synthesis of tropane alkaloids, such as DL-hyoscyamine [1], L-hyoscyamine [2,3], anisodamine [4][5][6], scopolamine [4,7], 6,7-dehydrohyoscyamine [7,8], and anisodine [9]. Stereochemical structure of acetyltropic acid is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%